Investigation of microstructure, mechanical and corrosion properties of GMAW of dissimilar P91-HP alloy V-butt groove joint - Atapek, S. Hakan; Tumer, Mustafa; Kisasoz, Alptekin; Mert, Tolga; Kerimak, Mithat Z. (ELSEVIER SCIENCE SA, 2024)
In this study, dissimilar metals HP iron-based nickel alloy and P91 creep resistant steel are welded with gas metal arc welding (GMAW) and microstructural, mechanical and corrosion properties of the joint are characterized. The findings show that (i) depending on the thermal cycle, columnar, cellular and equiaxed dendritic mor-phologies exist in the final solidification structure of the weld metal and there are Nb and Mo-rich carbides and Laves phases within interdendritic regions, (ii) highest stress concentration is in P91 region and a significant stress accumulates at the austenite grain boundaries of the nickel-based weld metal, (iii) a hardness value of 500 HV1 is reached in the HAZs of the base metals near the surface depending on the secondary phases, but the hardness decreases in the middle and root part of the joint due to the multiple temper effect, (iv) the least toughness is obtained in heat affected zone (HAZ) of HP alloy due to the presence of intermetallics along the grain boundaries and toughness of P91-HAZ is the highest (168 J), (v) fracture varied depending on tensile test temperature and both creep resistance characteristics of filler metal and P91 steel and also dissolution of Laves phase are decisive for the final rupture, (vi) in addition to considerably different corrosion resistance of the base metals, it is observed that the secondary phases in the weld metal reduce the corrosion resistance.
Keywords: HP alloy; P91; GMAW; ERNiCrMo-3; Microstructure; Mechanical properties; Corrosion; HIGH-TEMPERATURE BEHAVIOR; COAL POWER-PLANTS; BASE WELD METAL; STAINLESS-STEEL; LAVES PHASE; INCOLOY 825; INCONEL 718; WELDABILITY; DUCTILITY; Materials Science